Small ruminant genetic resources and parasite challenge in sub-Saharan Africa - Rey, B. (International Livestock Centre for Africa, 1991)
This overview aims at browsing the scene of action for research on the resistance of small ruminant to endoparasites in sub-Saharan Africa. After recalling the main sheep and goat breeds, it describes the geographic distribution of these populations in the continent, mentions the farming systems where they are found, and discusses the exposure to endoparasitism faced by these animals. In the last section, the knowledge of the economic and biological incidences of endoparasitism in Africa are briefly discussed.